Penerapan Persamaan Trend Surface Analysis untuk Pemisahan Anomali Residual dan Regional pada Data Gayaberat - Purwaditya Nugraha; Nono Agus Santoso (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2021)
The separation of regional anomalies and residual anomalies in gravity data is an important part in interpreting gravity data. This process aims to obtain gravity anomalies that have been associated with exploration targets. The Trend Surface Analysis method is a mathematical approach to the earth field that can be used to separate maps into regional components and local components. The application of this method into gravity data can be used to separate regional anomalies and residual anomalies. The process of processing the trend surface analysis method can be done using Microsoft Excel. This method is tested first on synthetic gravity data, the purpose of this test is to determine the performance of the trend surface analysis method in performing anomaly separation. Based on the test results of the trend surface analysis method on synthetic gravity data, it was found that this method was quite good at separating regional anomalies and residual anomalies. This is evidenced by the anomalous pattern that is already the same between the regional gravity anomaly resulting from the separation of the anomaly using the trend surface analysis method and the regional anomaly resulting from synthetic data. The same anomaly pattern can also be seen in the residual anomaly resulting from the separation of the anomaly using the trend surface analysis method with the residual anomaly resulting from synthetic data. The application of the trend surface analysis method to field data has been carried out by producing regional anomalies and residual anomalies. This method is very good at separating regional anomalies and residual anomalies, especially in regional anomalies located at deep depths.Pemisahan anomali regional dan anomali residual pada data gayaberat merupakan bagian penting dalam melakukan interpretasi data gayaberat. Proses ini bertujuan untuk mendapatkan anomali gayaberat yang sudah berasosiasi dengan target eksplorasi. Metode Trend Surface Analysis merupakan teknik pendekatan matematika pada bidang kebumian yang dapat digunakan untuk memisahkan peta kedalam komponen regional dan komponen lokal. Penerapan metode ini ke dalam data gayaberat dapat digunakan untuk memisahkan anomali regional dan anomali residual. Proses pengolahan metode trend surface analysis dapat dilakukan dengan menggunakan microsoft excel. Metode ini diuji terlebih dahulu pada data gayaberat sintetis, tujuan pengujian ini adalah untuk mengetahui performa metode trend surface analysis dalam melakukan pemisahan anomali. Berdasarkan hasil pengujian metode trend surface analysis pada data gayaberat sintetis didapatkan bahwa metode ini cukup baik dalam memisahkan anomali regional dan anomali residual. Hal ini dibuktikan pada pola anomali yang sudah sama antara anomali gayaberat regional hasil pemisahan anomali metode trend surface analysis dengan anomali regional hasil data sintetis. Pola anomali yang sama juga dapat dilihat pada anomali residual hasil pemisahan anomali metode trend surface analysis dengan anomali residual hasil data sintetis. Penerapan metode trend surface analysis pada data lapangan telah dilakukan dengan menghasilkan anomali regional dan anomali residual. Metode ini sangat baik dalam memisahkan anomali regional dan anomali residual terutama pada anomali regional yang berada pada kedalaman dalam